UPAYA PEMERINTAH INDONESIA DALAM MENANGANI PERDAGANGAN PAKAIAN BEKAS ILEGAL DARI SINGAPURA TAHUN 2015-2016 - Andrias, Qathru Nada; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In July 2015, Indonesia announced import banned second-hand clothes fromSingapore. Indonesia claims that Singapore second-hand clothes has been unfairlyflooding the Indonesian markets with cheap clothes product, so that impact toIndonesian worker and Indonesia Textile industries. The focus of this research is toanalyze the real motif Indonesia import banned on second hand clothes fromSingapore.This research uses Political Economy Theory related to Internasional Tradetheory which has been revealed by Hesckher-Ohlin. This research is Qualitativeresearch which is used by library observation.The result of this research prove that there’s several reason owned Indonesia toimpose banned on second-hand clothes product from Singapore. In Permendag 51/2015declared that health issue and unfair price that can cause distruption to local industryis the main reasons..The effort of indonesian goverment in limiting import second clothe ofsingapore to indonesian is by determinating import duty tax toward the second clothe ofsingapore to indonesian limiting import quota toward the second clothe of singapore toprotect local textil,and the indonesian goverment throught the cooperation of interinstitution such as customs/coast guard/an indonesian National Armed forces to preventthe smuggling of second clothe of singapore.Keywords: effort,trade,second clothe,protectsionism